A review of digital addiction and calling for safety education (2014)
In reviewing digital addiction, this paper recognize that digital technology has been useful in various sphere of life and the reach is undeniable, with an "average" user spending long hours on their phone or online daily. The demands of modern lifestyles have also lead to heavy dependence on various digital technologies for information, inter-personal relationships, entertainment and even economic transactions. There is no doubt that the over dependence on digital technology may result in addiction. Digital addiction is similar to other addictions; those suffering from it exhibit compulsive behavior and use the virtual fantasy world as a substitution for real-life human connection. Although all of its true effects are not known, the impacts on an addicted user's life are serious and may lead to social isolation, anxiety, depression, immune system disruption, brain damage and even death. Indeed, se are all at the receiving end of digital technology and deserve adequate safeguards and protections against the attendant risks of this technological revolution. In recommendations, health and safety education, time restriction and constant monitoring should be employed to safeguards health ways of using digital technology.